Lambang Penghambaan dan Penyucian dalam Al-Qur’an: Orientasi Waḥdah al-Wujūd Ibn ‘Arab dalam al-Futuḥāt al-Makkiyah - Ghozali, Mahbub (Jurnal Studi Al-Qur'an, 2022)
The complexity of the concept waḥdah al-wujūd in Ibn ‘Arabī understanding used in interpretation impacts the ignoring of his interpretation results leading to the essence of servitude and purification of God. The purpose of this study is the form of understanding that accentuates the meaning of the symbols depicted in verse. Tracing of Sufistic narratives in interpreting Ibn ‘Arabi was carried out in this study using qualitative methods with content analysis as a data analysis technique. The content analysis model analyzes the data by looking for conceptual relations in al-Futuḥāt al-Makkiyah by Ibn ‘Arabi about the Sufistic model of understanding. The semiotic theory of sacred texts aids this analysis process to see language phenomena in the scriptures presented through special symbols. This study found that the Sufistic interpretation of Ibn ‘Arabi is wrapped in symbolic form. The dressing of symbols in the process of understanding emphasizes the identification of Sufistic models with the diversion of meanings. This identity obscures Ibn ‘Arabī’s method of interpretation. The symbolic form is explained by analysis of the constitutional significance of the word writing and the function of his syntagmatic. The implications of this concept emphasize the relationship between God and servant (‘abd) implicit in each verse of the Qur’an. The result of the manifested interpretation underlines the totality of servitude and divinity, culminating in the level of the union of existence to God (waḥdah al-wujūd). Ibn ‘Arabī embodies the symbolic aspect represented in the Qur’an as a result of the decline of the language of God into the language of man.